Hyperfine structure measurements of Nb I and Nb II by Fourier transform spectroscopy. (December 2021) - Geng, Yidan; Jiao, Congcong; Yang, Zhihu; Gong, Yimin; Dai, Zhenwen
Highlights: Fourier transform (FT) spectra were used to extend the study of the hyperfine structure (HFS) of Nb I And Nb II energy levels. HFS constants A for 68 levels of Nb I from 11, 524.65 to 45, 719.07 cm−1 were determined, of which 26 results are reported for the first time, as far as we know. Our study increased the total number of HFS constants A to 349 Nb I levels. HFS constants A for 57 levels of Nb II from 2356.816 to 73, 869.773 cm−1 were determined, of which 46 results are reported for the first time, as far as we know. Our study increased the total number of HFS constants A to 99 Nb II levels. Abstract: Some of the archival data derived from the Fourier transform spectrometer (FTS) at the US National Solar Observatory ranging from 0 − 36, 947 cm −1 were investigated to study the hyperfine structure (HFS) patterns of Nb I and Nb II lines. The analysis of 155 lines in the FTS spectra was performed by a least squares fitting to derive values of the magnetic dipole HFS constant A . In total, the HFS constant A was determined for 68 levels of Nb I between 11, 524.65 and 45, 719.07 cm −1 and for 57 levels of Nb II between 2356.816 and 73, 869.773 cm −1 . 26 results for Nb I and 46 results for Nb II are reported for the first time, as far as we know.